2017
DOI: 10.1002/chir.22720
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of regioselectively substituted amylose derivatives for chiral separations

Abstract: Six novel regioselectively substituted amylose derivatives with a benzoate at 2-position and two different phenylcarbamates at 3- and 6-positions were synthesized and their structures were characterized by H nuclear magnetic resonance (NMR) spectroscopy. Their enantioseparation abilities were then examined as chiral stationary phases (CSPs) for high-performance liquid chromatography (HPLC) after they were coated on 3-aminopropyl silica gels. Investigations indicated that the substituents at the 3- and 6-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Another example is the resolution of racemate 5, which cannot be resolved on 1b (α, 1.00), was resolved on CTCMPC (α, 1.20). Investigations [7][8][9][10][11][13][14][15][16] have revealed that it is not unusual to obtain better resolutions with heterogeneously substituted polysaccharide derivatives and this phenomenon is also observed in this study. For instance, the α value for racemate 3 on 1b (2.41) was higher than that on CTCMPC (2.09).…”
Section: Enantioseparation Of Regioselectively Substituted Cellulose supporting
confidence: 80%
See 3 more Smart Citations
“…Another example is the resolution of racemate 5, which cannot be resolved on 1b (α, 1.00), was resolved on CTCMPC (α, 1.20). Investigations [7][8][9][10][11][13][14][15][16] have revealed that it is not unusual to obtain better resolutions with heterogeneously substituted polysaccharide derivatives and this phenomenon is also observed in this study. For instance, the α value for racemate 3 on 1b (2.41) was higher than that on CTCMPC (2.09).…”
Section: Enantioseparation Of Regioselectively Substituted Cellulose supporting
confidence: 80%
“…Among them, homogeneously substituted benzoates and phenylcarbamates of cellulose and amylose are the most often used materials, that is, they have the same substituent at the 2‐, 3‐, and 6‐positions of a glucose unit. In order to broaden the range of application on a same CSP, regioselectively substituted polysaccharide derivatives have also been utilized as CSPs in HPLC, leading to interesting data in regard of enantioselectivity [7–19]. CSPs based on regioselectively substituted polysaccharide derivatives were first reported by Kaida and Okamoto [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the recent advances in the development of chiral stationary phases contain chemical cross linking between the polysaccharide and silica supports, the enantiomeric analysis of underivatized ephedrines by using chiral columns has received a limited attention. So it is very much necessary to develop the direct methods for the separation and enantiomeric determination of ephedrines and ephedrine‐type compounds.…”
Section: Introductionmentioning
confidence: 99%